Adjusting the Religious Autobiography Course for the Postmodern Classroom - Ray, Darby Kathleen (Teaching theology and religion, 2000)
Religious autobiography as an introductory course is popular yet problematic. Often, it lacks methodological breadth and functions to ensconce Western notions of subjectivity which elide difference, locatedness, and the reality of multiple or shifting identifications. These problems can be addressed by incorporating into the course a community-based learning exercise in which each student is paired with a local senior citizen, conducts a series of interviews with the elder, and then writes an (auto-)biography based on the interviews. Students are thus given a real-life situation in which to test the applicability of theories and definitions of religion, as well as a relationship to a subject whose locatedness and relatively unprivileged “I” allow for the problematization of autobiography as a genre as well as an appreciation for the contextual nature of religiosity. This exercise transforms the religious autobiography course into a pedagogically fruitful, intellectually defensible, and institutionally savvy introductory course.